PARTISIPASI EFEKTIF DALAM PENGAMBILAN KEPUTUSAN PROGRAM KETAHANAN PANGAN DI TINGKAT DESA: PARTISIPASI EFEKTIF DALAM PENGAMBILAN KEPUTUSAN PROGRAM KETAHANAN PANGAN DI TINGKAT DESA - Putri Faridatun Nafisya; Hanny Purnamasari; Rachmat Ramdani (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
The food security program in Mekarjaya Village, implemented through the construction of a water reservoir and goat farm, is based on a participatory planning process. This study aims to analyze the forms and effectiveness of community participation, specifically in the decision-making dimension of the program. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model. The findings indicate that community participation in the decision-making stage is effective and high. This isindicated by the program's initiation by the Farmers' Group Association (Gapoktan) as a direct response to the irrigation crisis (the closure of the Pacinan River), as well as the involvement of group representatives in formal forums such as the Village Development Planning Meeting Musrenbang). This high level of participation in decision-making ensures that the selectedprograms (water reservoir and livestock) are fully demand-driven and align with the community's priority and real needs. This study concludes that the formal participation mechanism (Musrenbang) in Mekarjaya Village has been functioning optimally in ensuring theprogram's alignment with community needs.